DEVELOPMENT OF DIGITAL TEACHING MATERIALS BASED ON DIFFERENTIATED LEARNING USING CANVA FOR MATHEMATICS SUBJECTS - In Hi Abdullah; Dahlan Wahyudi; Winda Syam Tonra; Wilda Syam Tonra; Muhammad Hasbi (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kristen Indonesia, 2025)
Differentiated learning emphasizes that teachers must pay attention to students' learning differences and initial abilities. It is not easy for educators to deliver lessons in classrooms where students have varying skill levels and learning styles. The use of Canva facilitates all learning styles, whether auditory, visual, or kinesthetic. The application helps students understand lessons because, in addition to text, it also includes animations, audio, images, graphics, and videos, which keep students focused during class. The aim of this research is to develop digital teaching materials based on differentiated learning using Canva for mathematics subjects. The type of research conducted is R&D development using the 4-D model, which includes 1) Define, 2) Design, 3) Develop, and 4) Disseminate. Based on the analysis, the material validator test scored 82.1%, categorized as highly valid. The media validator test scored 88%, also categorized as highly valid, making the average validation test results meet the validity criteria. Additionally, the student response questionnaire regarding the digital teaching materials showed 82.9% positive responses, categorized as practical, and the evaluation test results showed that 80,44 of students achieved mastery, categorized as effective. Therefore, the digital teaching materials based on differentiated learning assisted by Canva meet the criteria of being valid, practical, and effective.